Print Media Coverage of Environmental Issues in the COVID-19 Pandemic: An Ecolinguistic Analysis - Mlilesss Mohamed; Mohammed Larouz (JURNAL ARBITRER, 2020)
The coverage of environmental issues is of great importance to Moroccan newspapers, namely As-Sabah, Al-Akhbar, and Al-Massae. The present study explores the frequency of articles that covered environmental issues and investigated the newspapers' professionalism in writing environmental reports on man's environmental setting violations. The Research was accomplished through the framework of ecolinguistics to categorize and analyze all environmental stories that extended from March to July 2020. The sums of 308 issues of the three newspapers were manually checked to identify the issues reported about environmental problems. The findings revealed that environmental coverage by the three newspapers was feeble. Precisely, only 73 newspaper issues pertaining to the three newspapers contained at least one environmental title. Practically, identified environmental articles were manually searched and treated based on a keyword selection such as environment, forest, animals, water, pollution, air, irrigation, deforestation, and overgrazing, among other words. In total, the final sum of environmental articles published by the three newspapers during the COVID-19 period were 92 articles (1.8%) over 4922 total articles published by 73 issues. The role of print media is determinant in covering environmental topics to maintain the public informed about the protection of environmental resources during the COVID-19 pandemic. Unfortunately, this role is far from being achieved given the feeble interest devoted to environmental issues and the way through which the newspapers have produced environmentally based stories. To remedy this situation, some recommendations are afforded to improve the writing of environmental reports in line with ecolinguistics principles and environmental journalism ethics.